The Influence Of Marketing Strategy On Interest In Savings At Bank Mega Mamuju Branch Office - Nikia , Nikia; Amalia, Amalia; Kamarudin , Jamaludin (Jurnal Economic Resource, 2025)
This study aims to determine the effect of marketing strategy variables on interest in saving at Bank Mega Mamuju Branch Office. The research method used is a quantitative method with primary data using a questionnaire. Respondents in the study were all customers at Bank Mega Mamuju Branch Office with a population of 726 customers, the sample used was the Probability Sampling technique, and the number of samples was determined using the Slovin formula with a sample of 88 respondents. The formula used in this study is validity test, reliability test, multiple linear regression, t test and coefficient of determination test (R2). The results of this study indicate that marketing strategy (X) has a significant partial effect on interest in saving (Y) at Bank Mega Mamuju Branch Office and marketing strategy (X) has a correlation with interest in saving (Y) mega fund savings products at Bank Mega Mamuju Branch Office